PENGEMBANGAN MEDIA KARTU DOMINO UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SD - Atikah Muthoharoh; Tety Nur Cholifah (STKIP Persada Khatulistiwa Sintang, 2020)
The purpose of this study is determine the feasibility of domino card learning media in thematic learning and find out the suitability of domino cards to increase learning motivation of fourth grade elementary school students. This research is development research using the Borg and Gall model. The research was conducted at SDN Permanu 02 with the subject of 33 fourth grade students for the 2019/2020 school year. The results showed the feasibility of domino card learning media based on material validation, media validation, group response trials and large group student response trials getting an average rating of 89% with very valid qualifications. The results of student learning motivation in small groups showed the percentage before 58%with enough categories, after the percentage of 89% with very high category.The results of student learning motivation in large groups showed before the percentage of 39% with the low categoryand after percentage of 76%with high category. Based on the data mentioned above, it can be concluded that the domino card learning media is suitable for use in the learning process and can increase the learning motivation of grade IV SD students